An “Entirely Different” Kind of Union: The Service, Office, and Retail Workers’ Union of Canada (SORWUC), 1972–1986 - Smith, Julia (Labour / Le Travail, 2014)
In this article I examine the Service, Office, and Retail Workers’ Union of Canada (SORWUC), an independent, grassroots, socialist-feminist union that organized workers in unorganized industries in Canada in the 1970s and 1980s. I look at sorwuc’s role in Canadian labour history in general, and its efforts to organize workers in the service industry in particular. My central thesis is that sorwuc’s socialist-feminist unionism and commitment to organizing unorganized workers positioned the union as radically different from the mainstream labour movement. This difference both helped and hindered the union. Specifically, sorwuc’s experiences organizing workers at Bimini pub and Muckamuck restaurant in British Columbia demonstrate that although its alternative structure and strategies aided organizing and strike efforts, these factors made little difference in the union’s dealings with the labour relations boards and the courts: in both cases, the action or inaction of the state ultimately determined the outcome. Although sorwuc no longer exists, it remains an important historical example of how workers in Canada have been and can be organized. sorwuc thus offers important lessons about service worker organizing, alternative forms of unionization, and the powerful role of the state in labour relations in the postwar period.